Obesity and the lung: 2 · Obesity and sleep-disordered breathing. Issue 8 (28th July 2008) - Crummy, F; Piper, A J; Naughton, M T
Abstract : As the prevalence of obesity increases in both the developed and the developing world, the respiratory consequences are often underappreciated. This review discusses the presentation, pathogenesis, diagnosis and management of the obstructive sleep apnoea, overlap and obesity hypoventilation syndromes. Patients with these conditions will commonly present to respiratory physicians, and recognition and effective treatment have important benefits in terms of patient quality of life and reduction in healthcare utilisation. Measures to curb the obesity epidemic are urgently required.